2016
DOI: 10.5812/ircmj.24809
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Traditional Medicine Product Henna and Hydrocortisone on Diaper Dermatitis in Infants

Abstract: BackgroundDiaper dermatitis (DD) is a common inflammatory disorder in infants, including newborns.ObjectivesThis study aimed to compare the effects of a traditional medicine product (containing natural henna oil 25%) and hydrocortisone 1% cream on DD in infants.Patients and MethodsIn a triple-blind, randomized trial, 82 children aged two years or less were randomly divided into two groups of 41 children each to receive either hydrocortisone ointment or henna medicinal product. Infants were treated 3 times a da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…In the intervention group, the average area of pressure ulcer on the 7 th day decreased significantly as compared with the 1 st day; it also had a significant difference on the 1 st , 4 th , and 7 th days. In[ 7 ] the effectiveness of henna and hydrocortisone 1% ointment on recovery of diaper dermatitis was examined. The results suggested that henna was more effective than hydrocortisone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the intervention group, the average area of pressure ulcer on the 7 th day decreased significantly as compared with the 1 st day; it also had a significant difference on the 1 st , 4 th , and 7 th days. In[ 7 ] the effectiveness of henna and hydrocortisone 1% ointment on recovery of diaper dermatitis was examined. The results suggested that henna was more effective than hydrocortisone.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that henna was more effective than hydrocortisone. [ 7 ] In addition, the results of a study on the effect of henna in the prevention of pressure ulcers in ICUs indicated that henna can prevent the occurrence of pressure ulcers by reducing local temperature and inflammation of the sacral region. [ 8 ] Another research evaluated the effect of henna leaf extract on cutaneous ulcer in Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have been carried out regarding the use of other complementary and traditional treatments such as henna (Keshavarz et al 2016), the combination of honey, wax and olive oil (El Sakka, Abdulrhman & Shehata 2013), aloe vera (Panahi et al 2012), bentonite (Mahmoudi, Adib-Hajbagheri & Mashaiekhi 2015), clay shampoo (Adib-Hajbagheri, Mahmoudi & Mashaiekhi 2014), and anti-hemorrhoid ointment (Liu & Xie 2012), but more studies still need to be done in this topic. Keshavarz et al (2016) conducted a randomized tripleblinded study in 2016 to compare the effects of a tradi-tional drug containing henna 25% and hydrocortisone 1%. In this study, 82 (41 in each group) healthy children under the age of two years suffering from diaper dermatitis were studied and used the drug 3 times a day for 5 days in the area of diaper dermatitis.…”
Section: Sunflower Oilmentioning
confidence: 99%